Cover Feature: Widely Electronically Tunable 2, 6‐Disubstituted Dithieno[1, 4]thiazines—Electron‐Rich Fluorophores Up to Intense NIR Emission (Chem. Eur. J. 57/2020). Issue 57 (4th September 2020) - May, Lars; Müller, Thomas J. J.
Abstract : NIR‐emission depends on the right isomer. While the syn ‐ syn ‐dithienothiazine dye is only weakly emissive, the anti ‐ anti isomer intensively emits in the NIR with a fluorescence quantum yield of 52 %. Literally switching the isomer furnishes this peculiar photophysical characteristic. More information can be found in the Full Paper by L. May and T. J. J. Müller on page 12978 .